Efficacy of a terpinen-4-ol based dipping for post-milking teat disinfection in the prevention of mastitis in dairy sheep. Issue 1 (2nd January 2019) - Dore, Simone; Ferrini, Anna Maria; Appicciafuoco, Brunella; Massaro, Maria Rosa; Sotgiu, Giovanni; Liciardi, Manuele; Cannas, Eugenia Agnese
ABSTRACT: Mastitis is the main cause of antibiotic use in dairy sheep. Post-milking teat disinfection is adopted to prevent intra-mammary infections. Use of chemical disinfectants is associated with biocide and antibiotic resistance. Terpinen-4-ol (T-4-ol), component of the Melaleuca alternifolia essential oil, shows antibacterial properties without inducing resistance. Aim of the trial was to evaluate the efficacy of a T-4-ol post-dipping compound in preventing bacterial mastitis in dairy sheep. In two different farms, two groups of 35 ewes were recruited as experimental and control arm (exposed to chlorhexidine-based disinfectant). No differences were observed during the follow-up. In one livestock, during the first year, 30-day incidence of mastitis was significantly lower in the T-4-ol group. Post-milking teat disinfection with T-4-ol showed equivalent efficacy in terms of mastitis incidence. Disinfectants based on natural compounds for mastitis prevention could potentially reduce environmental pollution, avoid drug residues in milk and decrease the antimicrobial resistance development.